Effects of a high salt diet on blood pressure dipping and the implications on hypertension - Viggiano, Jesse; Coutinho, Dominic; Clark-Cutaia, Maya N.; Martinez, Diana (Frontiers in Neuroscience, 2023)
High blood pressure, also known as hypertension, is a major risk factor for cardiovascular disease. Salt intake has been shown to have a significant impact on BP, but the mechanisms by which it influences the blood pressure dipping pattern, and 24-h blood pressure remains controversial. This literature review aims to both summarize the current evidence on high salt diet induced hypertension and discuss the epidemiological aspects including socioeconomic issues in the United States and abroad. Our review indicates that a high salt diet is associated with a blunted nocturnal blood pressure dipping pattern, which is characterized by a reduced decrease in blood pressure during the nighttime hours. The mechanisms by which high salt intake affects blood pressure dipping patterns are not fully understood, but it is suggested that it may be related to changes in the sympathetic nervous system. Further, we looked at the association between major blood pressure and circadian rhythm regulatory centers in the brain, including the paraventricular nucleus (PVN), suprachiasmatic nucleus (SCN) and nucleus tractus solitarius (nTS). We also discuss the underlying social and economic issues in the United States and around the world. In conclusion, the evidence suggests that a high salt diet is associated with a blunted, non-dipping, or reverse dipping blood pressure pattern, which has been shown to increase the risk of cardiovascular disease. Further research is needed to better understand the underlying mechanisms by which high salt intake influences changes within the central nervous system.